Kendali Budget Ketat pada Pemda Di Provinsi Bali dalam Menghadapi Turbulensi Budget - Wirasedana, I Wayan Pradnyantha; Sisdyani, Eka Ardhani; Setiawan, I Putu Ery (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p12, 2018)
This research aimed to provide recommendation on how stringent or flexible budget control held by district government, especially in Bali Province, so that deficits or surpluses can be avoided and budget performance improved. The data were collected from multiple methods including survey using questionnaire, observation, budget archive verification, budget realization report and macro economic data from Badan Pusat Statistik Provinsi Bali. The population was district and town governments in Bali Province and purposive sampling was used, based on Klassen Typology.  The data was tested to estimate measurement and structural models using Partial Least Square (PLS) method and interaction effect test using Ordinary Least Square (OLS) method. The result of this research can be used to anticipate contingency factor such as budget turbulence in guaranteeing budget efficiency, especially when budget turbulence affect the relationship of stringent budget control and budget deviation. Keywords: stringent budget control, budget turbulence, district and town governments